Study of Management of Cerebrospinal Fluid Rhinorrhea - Raval, Himanshu (Indian Journal of Neurosurgery, 2021)
Cerebrospinal fluid (CSF) rhinorrhea is a condition where the protective fluid that surrounds the brain finds its way into the nose and sinuses, often appearing as a very watery runny nose. In this study, we are looking for clinical picture, various available investigation and treatment modalities, and their outcomes. In this study, we include 60 patients diagnosed with CSF rhinorrhea irrespective of cause. Patient having similar clinical picture but ruled out by investigation are not included. We obtain result in terms of most common causative factor, common site, and efficacy of treatment, and can decide a favorable line of management with respect to different circumstances.
Keywords: CSF; CSF rhinorrhea; trauma; intracranial; extra cranial